Safety management systems from Three Mile Island to Piper Alpha, a review in English and Dutch literature for the period 1979 to 1988. (August 2018) - Swuste, Paul; Groeneweg, Jop; van Gulijk, Coen; Zwaard, Walter; Lemkowitz, Saul
Highlights: No relation existed between management approaches, safety theories, and safety performance. Human errors explaining occupational accidents are still popular in the professional press. Process safety outplaced the developments in occupational safety, which was leading before. In process safety, human errors were the result of suboptimal interactions during disturbances. Theories and models were unable to predict probabilities, and scenarios of future disasters. Abstract: Objective: Which general management and safety models and theories trends influenced safety management in the period between Three Mile Island in 1979 and Piper Alpha in 1988? In which context did these developments took place and how did this influence Dutch safety domain? Method: The literature study was limited to original English and Dutch documents and articles in scientific and professional literature during the period studied. Results and conclusions: Models and theories of human errors, explaining occupational accidents were still popular in the professional literature. A system approach was introduced into mainstream safety science, starting in process safety, and subsequently moving into occupational safety. Accidents were thought to be the result of disturbances in a dynamic system, a socio-technical system, rather than just human error. Human errors were also perceived differently: they were no longer faults of people, but consequences of suboptimal interactions during process disturbances. In this period quality of safety research increased substantially, also in the Netherlands. Major disasters in the 1980s generated knowledge on process safety, and soon process safety outplaced developments in occupational safety, which had been leading before. Theories and models in this period had advanced sufficiently to explain disasters, but were still unable to predict probabilities and scenarios of future disasters. In the 1980s 'latent errors' appeared in safety literature, and in The Netherlands the concept of 'impossible accidents' appeared. Safety management was strongly influenced by developments in quality management.